Implicit Essentialism: Genetic Concepts Are Implicitly Associated with Fate Concepts - Gould, Wren A.; Heine, Steven J. (PLOS ONE, 2012)
Genetic essentialism is the tendency for people to think in more essentialist ways upon encountering genetic concepts. The current studies assessed whether genetic essentialist biases would also be evident at the automatic level. In two studies, using different versions of the Implicit Association Test [1], we found that participants were faster to categorize when genes and fate were linked, compared to when these two concepts were kept separate and opposing. In addition to the wealth of past findings of genetic essentialism with explicit and deliberative measures, these biases appear to be also evident with implicit measures